1993
DOI: 10.1038/bjc.1993.314
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck sarcomas: prognostic factors and implications for treatment

Abstract: (Robinson et al., 1992).The following data were also collected: demographic factors, tumour stage (UICC), predisposing factors, treatment details, and local recurrence plus overall survival. Actuarial plots of survival and local recurrence-free rate, according to the above facors, were compared using log-rank analysis (Peto et al., 1977). Multivariate Cox regression analysis was carried out to determine the independent prognostic factors for survival and local recurrence (Cox, 1972). Death was not treated as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
1
7

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(134 citation statements)
references
References 24 publications
10
116
1
7
Order By: Relevance
“…Recent examples published in this journal include studies of patients with primary cerebral lymphoma (Blay et al, 1993), head and neck sarcomas (Eeles et al, 1993) and testicular cancer (Steyerberg et al, 1993). In some cases such studies may offer insight into the molecular pathogenesis of the disease.…”
mentioning
confidence: 99%
“…Recent examples published in this journal include studies of patients with primary cerebral lymphoma (Blay et al, 1993), head and neck sarcomas (Eeles et al, 1993) and testicular cancer (Steyerberg et al, 1993). In some cases such studies may offer insight into the molecular pathogenesis of the disease.…”
mentioning
confidence: 99%
“…[3] Liposarkomlar baş boyun bölgesinde sıklıkla çene (%14), boyun orta hat (%13), larenks ve priform sinüs (%13), orbita (%8) ve supraglottik (%7) bölgede görü-lür. [12] Baş boyun bölgesi liposarkomları genellikle yutma güçlüğü ve üst solunum yolları obstrüksiyonu bulguları ile ortaya çıkar. Ozawa ve ark.…”
Section: Discussionunclassified
“…Bununla birlikte Eeles ve ark. nın [12] yaptıkları bir çalışmada radyoterapinin lokal nüksü azalttığı ancak metastaz ve sağkalımı etkilemediği gösterilmiştir.…”
Section: Praxis Of Orlunclassified
“…The most common age of presentation is between 50 and 60 years, ranging from 15 to 93 years, only the study of Eeles et al [7] shows age of onset below 40 years, although their series included patients from 3 years old, decreasing the average age; the series of Kraus et al [18] and Chen et al [22] demonstrated mean age of onset \50 years and the rest we see that the average age is 50 years. In our series the proportion of male-female condition is 2.3 -1 and the average age of presentation is 38.9 years.…”
Section: Clinical Features and Presentationmentioning
confidence: 92%
“…The knowledge that we currently have in head and neck sarcomas is based in classic series that began decades ago in which there are misclassification in up to 39% of the population [1,7] and there are not series published to date of maxillary sinus sarcomas .…”
Section: Introductionmentioning
confidence: 99%